An edge-based smoothed finite element method for semi-implicit coupling of unsteady viscoelastic fluid–structure interaction. (June 2023) - He, Tao; Ma, Xi
Highlights: A mass source term is derived from the modified continuity equation. Geometric conservation law is satisfied in edge-based smoothed finite element method. An efficient and stable semi-implicit coupling scheme is presented accordingly. Viscoelastic fluid–structure interaction is modeled by variable-node smoothing cells. Abstract: In this paper, a new partitioned semi-implicit coupling algorithm is developed for unsteady viscoelastic fluid–structure interaction in association with an edge-based smoothed finite element method (ESFEM). Stabilization techniques tailored for the viscoelastic fluid subproblem are naturally integrated into the hybrid explicit/implicit coupling framework to achieve the enhanced stability. In particular, a mass source term derived from the modified continuity equation in the finite-element context enables the ESFEM to fulfill the geometric conservation law on variable-node smoothing cells during the subiterations. Moreover, both multi-field equations and interface conditions are easily discretized with the ESFEM which enjoys high flexibility of smoothed Galerkin weak-form integral. Desirable numerical results are given for two benchmark problems.